Enhancement of Satya Budi Farm's Revenue through the Implementation of Complete Feed Technology with Direct Fed Microbials Supplementation - Suryani, Heni; Maria Sinaga, Desi; Desmiyeni Putri, Dwi; Silaban, Rikardo; Pramesti Tandayu, Laras; Haya Nazaha, Hanifah (J-Dinamika : Jurnal Pengabdian Masyarakat, 2025)
This activity is a part of Creative Innovation programs for Vocational Partners which aims to increase the knowledge and skills of Satya Budi Farm partners in utilizing local feed ingredients and Direct Fed Microbials (DFM). Apart from that, this activity aims to increase Satya Budi Farm's income through the sale of cattle and feed. Descriptive and quantitative approaches are used in analyzing Satya Budi Farm's profits. The series of activities in this program are complete feed (CF) formulation training by prioritizing local feed ingredients, DFM training and production to increase feed efficiency, Business Analysis Calculation Method. The results of this activity show that Satya Budi Farm's profit for the 3 months before the program started was IDR. 2,006,644.8/head/month while the profit after the program runs is IDR. 2,712,327.4/head/month. So, there is an increase in profit per head per month of 35.17%.